A Firefly Algorithm Based Approach for Automated Generation and Optimization of Test Cases - Sahoo, Rajesh Kumar; Mohapatra, Durga Prasad; Patra, Manas Ranjan (International Journal of Computer Sciences and Engineering, 2025)
Software testing requires functional and non functional test cases with the values of test data.Automated testing are a method to generate the test cases with test data automatically. Optimality of test case is required for fastest data generation. Test case optimization through search based techniques is used to optimize and generate optimal test cases from the set of data values. Firefly Algorithm (FA) is a bio-inspired, evolutionary, meta-heuristic algorithm based on mating or flashing behavior of fireflies. In this paper the role of Firefly meta-heuristic search technique which is analyzed to generate and optimize random test cases with test data by applying in a case study, i.e., a withdrawal method in Bank ATM and it is observed that this algorithm is able to generate suitable automated test cases as well as test data. In this case the test case generation is very efficient and effective. This paper further, gives the brief details about the Firefly method which is used for test case generation and optimization.